Implementation of child-friendly schools (SRA) in inclusive schools: A literature review - SAIDI, NOVIANTI; Yoenanto, Nono Hery; Nawangsari, Nur Ainy Fardana (Talenta Publisher, 2024)
Several schools in Indonesia organized inclusive schools to create a comfortable school environment for children, and a child-friendly school program (SRA) was established. This study aims to identify the successful implementation of SRA in inclusive schools. The research method used was a systematic literature review (SLR) with the stages of PICO formation, language terminology, inclusion and exclusion criteria, and PRISMA 2020 to search and filter literature according to the inclusion criteria. This study's results show that several main factors, such as bureaucracy, curriculum suitability, teacher competence and mastery, and adequate school facilities and infrastructure, can help realize the success of SRA in inclusive schools.